Antitumor effects of the small molecule DMAMCL in neuroblastoma via suppressing aerobic glycolysis and targeting PFKL - Simeng Zhang (BMC, 2021)
Abstract Background Neuroblastoma (NB) is a common solid malignancy in children that is associated with a poor prognosis. Although the novel small molecular compound Dimethylaminomicheliolide (DMAMCL) has been shown to induce cell death in some tumors, little is known about its role in NB. Methods We examined the effect of DMAMCL on four NB cell lines (NPG, AS, KCNR, BE2). Cellular confluence, survival, apoptosis, and glycolysis were detected using Incucyte ZOOM, CCK-8 assays, Annexin V-PE/7-AAD flow cytometry, and Seahorse XFe96, respectively. Synergistic effects between agents were evaluated using CompuSyn and the effect of DMAMCL in vivo was evaluated using a xenograft mouse model. Phosphofructokinase-1, liver type (PFKL) expression was up- and down-regulated using overexpression plasmids or siRNA. Results When administered as a single agent, DMAMCL decreased cell proliferation in a time- and dose-dependent manner, increased the percentage of cells in SubG1 phase, and induced apoptosis in vitro, as well as inhibiting tumor growth and prolonging survival in tumor-bearing mice (NGP, BE2) in vivo. In addition, DMAMCL exerted synergistic effects when combined with etoposide or cisplatin in vitro and displayed increased antitumor effects when combined with etoposide in vivo compared to either agent alone. Mechanistically, DMAMCL suppressed aerobic glycolysis by decreasing glucose consumption, lactate excretion, and ATP production, as well as reducing the expression of PFKL, a key glycolysis enzyme, in vitro and in vivo. Furthermore, PFKL overexpression attenuated DMAMCL-induced cell death, whereas PFKL silencing promoted NB cell death. Conclusions The results of this study suggest that DMAMCL exerts antitumor effects on NB both in vitro and in vivo by suppressing aerobic glycolysis and that PFKL could be a potential target of DMAMCL in NB.